2009
DOI: 10.1063/1.3089569
|View full text |Cite
|
Sign up to set email alerts
|

Telegraph noise due to domain wall motion driven by spin current in perpendicular magnetized nanopillars

Abstract: Articles you may be interested inCurrent-driven domain wall motion across a wide temperature range in a (Ga,Mn)(As,P) device Appl. Phys. Lett. 97, 262102 (2010); 10.1063/1.3532095 Current-induced domain wall motion in a nanowire with perpendicular magnetic anisotropy Appl. Phys. Lett. 92, 202508 (2008); 10.1063/1.2926664 Current driven domain wall motion in magnetic U-pattern J. Appl. Phys. 97, 10C710 (2005); 10.1063/1.1852872 Circular domain wall motion driven by spin-polarized currents in confined square nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The principal possibility of driving domain walls using currents was confirmed experimentally for L-shaped elements [63,64], for ring-shaped [65,66] and straight [67] structures with constrictions, and in multilayer wires [68]. While most studies were performed on Py, also magnetic semiconductors [69][70][71] and materials with out-of-plane magnetization [72][73][74][75][76][77][78][79][80] were investigated. The discovery of current-driven domain wall motion led to the suggestion that the effect might be employed as a new generation of storage devices (so-called Racetrack memory, see [81] for a review).…”
Section: Spin-torque In Lateral Structures: Current-induced Domain Wamentioning
confidence: 99%
“…The principal possibility of driving domain walls using currents was confirmed experimentally for L-shaped elements [63,64], for ring-shaped [65,66] and straight [67] structures with constrictions, and in multilayer wires [68]. While most studies were performed on Py, also magnetic semiconductors [69][70][71] and materials with out-of-plane magnetization [72][73][74][75][76][77][78][79][80] were investigated. The discovery of current-driven domain wall motion led to the suggestion that the effect might be employed as a new generation of storage devices (so-called Racetrack memory, see [81] for a review).…”
Section: Spin-torque In Lateral Structures: Current-induced Domain Wamentioning
confidence: 99%
“…First of all it could be shown that by tuning the anisotropy of [Co/Ni] for nanopillars with spin valve structure, the critical currents for spin torque could be further reduced, while thermal stability was maintained, what is a key point towards applications [39,40]. Another studied effect was the creation of domain walls in nanostructures driven by spin-polarized currents [41] and concomitant telegraph noise [42].…”
Section: Introductionmentioning
confidence: 99%
“…This can occur either through direct reflection when DW width ∆ ∼ λ F [16], or by spin-dependent scattering of electrons by the disorder inside the DWs [17,18]. Recently, the fluctuations in R in different forms of nano-magnetic structures have been associated with the motion of DWs [19,20], although the details of the time dependence of R due motion of individual DWs remain unexplored.…”
mentioning
confidence: 99%